(untitled) (Texas Journal of Philology, Culture and History, 2026)
This article examines the processes of adaptation of immigrants visiting the Republic of Uzbekistan for various purposes to the social environment, their philosophical and sociological foundations. The article highlights the essence of the concept of adaptation, the specific cultural and spiritual environment of Uzbekistan and the role of state policy in the integration of immigrants. It also analyzes the importance of national values and principles of tolerance in the adaptation of immigrants